Analisa Dan Perancangan Sistem Pendukung Keputusan Penentuan Promosi Jabatan Pada PT. XYZ Menggunakan Metode Profile Matching - Sari, Mawar (Department of Informatics, Siliwangi University, Indonesia, 2022)
Human Resources (HR) is one of the important functions in an organization or company to get the best employees to achieve the goals of the company. The best way how to improve Human resources is by promoting or awarding the best employees. The selection of the best employees is required an objective system. PT. XYZ is one of company who implementing these methods to improve their resources, but the selecting are still conventional methods which final decision still determined under leadership company according to the existing delegation of authority. This research is to analyze and design a decision support system to determining the promotion using Profile Matching Method. the implementation will be two main aspect that will be assessed, they are Performance Aspects and work behavior aspect, each aspect has 5 sub-criteria. The final value of two aspects is calculated with different percentage which are 70% for the performance aspect and 30% for work behavior aspect. The results, there were 3 employees with the highest grades who entitled to be promoted, are the employee with NIK INDO09, INDO07 and INDO06 which score of 4,81, 44,62 and 4,49. Finally the decision support system implemented to the web-based application which expected to assist related parties in determining employee promotions based on specified criteria to get the objective decisions.